Wychowanie do człowieczeństwa Eduarda Sprangera - Zieliński , Paweł (Studia Edukacyjne, 2023)
The author reconstructs and interprets the Education to Humanity by Eduard Spranger, a prominent German philosopher, psychologist, and pedagogue, whose pedagogical work is little known in Poland. The barbarism of the Russian-Ukrainian War is a reminder of how topical the issue of realising the value of humanity is in contemporary education. Spranger not only answers the question of what humanity is, but points to specific, rather than general, methods of its formation in young people. He refers to selected teaching methods of Socrates, specifically to moral stories, and also to meditation, as in Zen Buddhism. He links a number of universal values to the formation of humanity, such as self-reflection, dignity of the person, self-criticism, responsibility, conscience, and love. Spranger’s theory of upbringing is holistic. Its teleology is oriented towards personality development, with an emphasis on altruistic values and human moral development. It is largely consistent with the pedagogical thought of Otto F. Bollnow, Abraham H. Maslow, Theodor Adorno, Hans Waldenfens, Andrzej Szyszko-Bohusz, Hilarion G. Petzold and other contemporary scholars – humanists. It also seems a continuation of Immanuel Kant’s, Johann H. Pestalozzi’s, Leo N. Tolstoy’s, Rudolf Steiner’s and even Mencius’s concepts of education, as well as those of Zen and Daoist teachers. Spranger opposed the idea of a transhumanism based on modern technology, as well as the instrumental and utilitarian treatment of nature, and the materialistic and technological trend, that is omnipresent in modern human life.